'I Sat Filling in This Form While Smoking and It Was Divine'. An Analysis of Free-Text Comments from Smokers Who Report They Have No Intention of Quitting in the Next Six Months. (16th December 2014) - Sweeney-Magee, M.; Kale, D.; Hamill, A.; Gilbert, H.
Abstract : Introduction: Smokers unmotivated to quit are neglected by smoking cessation research. Free-text comment analysis is a potentially useful way to gain insight into this group's beliefs. Aims: To analyse the free-text comments provided by smokers unmotivated to quit as part of a randomized controlled trial of computer-tailored feedback for smoking cessation. Method: A random sample of 58, 660 smokers were sent a smoking behaviour questionnaire (SBQ). The responses and follow-up outcomes of those providing free-text comments were compared to those who did not to assess the representativeness of the former group of smokers. The comments of participants unmotivated to quit (631) were thematically analysed. Results: Those who provided a comment differed from those who did not on variables including education level and quit attempts at six-month follow-up. Emergent themes included; justification of smoking and restricting smoking instead of quitting. Conclusions: The findings illustrate the value of free-text comments in identifying issues important to respondents. The identified themes highlight areas for future research in smokers unmotivated to quit including cutting down as a path to quitting and explicit messages regarding the inability of positive health behaviours to balance out the negative impact of smoking on health. Trial registration: Current Controlled Trials ISRCTN05385712.